(3TQM GHf HWGd Ydi GdHNGQis - (3Ydj Hf Nda Hf YHO Gdedc Hf HWGd GdeZQHj GdbQWHi GdeGdcj , GHf nHnqWGd , J (B449 (3g` s; (3eSde Hf GdMLGL Hf eSde GdbTjQj GdfjSGHhQqi, CHh GdMSjf,J (B261 (3g` s
(3ChdgG (B:s
(3hLhH GdRcGI hbhd Gddg YR hLd hCbjehG GdUdGI hCJhG GdRcGg s
(3BNQgG (B:s
(3GfJgi GdSaQ GdQGHY ef gPG GdTQM s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdMOjK h GdeUWdMs